Surgical stress and metabolic response after totally laparoscopic right colectomy - Milone, Marco (Sci Rep, 2021)
No clear consensus on the need to perform an intracorporeal anastomosis (IA) after laparoscopic right colectomy is currently available. One of the potential benefits of intracorporeal anastomosis may be a reduction in surgical stress. Herein, we evaluated the surgical stress response and the metabolic response in patients who underwent right colonic resection for colon cancer. Fifty-nine patients who underwent laparoscopic resection for right colon cancer were randomized to receive an intracorporeal or an extracorporeal anastomosis (EA). Data including demographics (age, sex, BMI and ASA score), pathological (AJCC tumour stage and tumour localization) and surgical results were recorded. Moreover, to determine the levels of the inflammatory response, mediators, such as C-reactive protein (CRP), tumour necrosis factor (TNF), interleukin 1β (IL-1β), IL-6, IL-10, and IL-13, were evaluated. Similarly, cortisol and insulin levels were evaluated as hormonal responses to surgical stress. We found that the proinflammatory mediator IL-6, CRP, TNF and IL-1β levels, were significantly reduced in IA compared to EA. Concurrently, an improved profile of the anti-inflammatory cytokines IL-10 and IL-13 was observed in the IA group. Relative to the hormone response to surgical stress, cortisol was increased in patients who underwent EA, while insulin was reduced in the EA group. Based on these results, surgical stress and metabolic response to IA justify advocating the adoption of a totally laparoscopic approach when performing a right colectomy for cancer. This trial is registered on ClinicalTrials.gov (ID: NCT03422588).